Application of Refractive Index Mixing Rules in Binary Liquid Mixtures - Saxena, M.C.; Tripathi, Ashutosh (Asian Journal of Chemistry, 2010)
A comparative study of five mixing rules of refractive index has been carried out to test their validity for five binary liquid mixtures at a wide range of compositions at 298.15 K. Comparison of various rules has been expressed in terms of average percentage deviation. All the mixing rules perform well within the limit of experimental error but performance of Lorentz-Lorenz (L-L) and Gladstone-Dale (G-D) relation is comparatively better than those of others.